Novel Chemical Modalities and Methods for Protein Profiling - McKenna, Sean Martin (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2024)
The activity of proteins is pivotal to the chemistry of cells. In order to deconvolute the complexity of living systems, chemical tools can be used to study active proteins under different cellular states. Amongst these chemical tools, activity based probes and affinity based probes enable proteins in complex biological systems to be covalently labelled and studied. Presented here are investigations into several novel chemical modalities for protein labelling, and their applications in protein profiling studies. In the first chapter, key methods in bioconjugation chemistry and activity-based protein profiling are introduced. Deubiquitinating enzymes are highlighted as key regulators in cellular signalling, and a suite of activity-based probes for the study of deubiquitinases are discussed. Opportunities for the development of new chemical tools for profiling deubiquitinating enzymes and other proteins of interest are also summarised. The development of a novel class of photoactivatable affinity based probes for profiling members of the metalloproteome are described in the second chapter. In this investigation, a set of probes featuring a rarely utilised metal chelator were prepared to examine a class of understudied metalloproteins. Proof of concept labelling experiments were performed on a model zinc metalloprotease, and translation of the probe to labelling experiments in complex biological systems was accomplished. Probes were used to label metalloproteins in living cells, and proteomic analysis identified several therapeutically significant binding partners. Amongst these were members of a helicase complex which enables pre-mitotic DNA replication. Further studies revealed that cells treated with the novel affinity based probe experienced stalling in their DNA replication cycle, consistent with disruption of the helicase complex. This work highlights a novel cellular function for the metal chelator, as well as broader applications for the study of other therapeutically significant metalloproteins. In the third chapter, applications of the thiol-ene reaction were explored as tools for bioconjugation. In this study, new radical acceptor motifs were investigated as olefin replacements in activity-based probes for deubiquitinating enzymes. A set of ring strained warheads were found to be ineffective radical acceptors in a thiol ene bioconjugation study. However, in the course of this work, a weak labelling effect between ubiquitin-containing probes and a deubiquitinating enzyme was detected under thiol ene reaction conditions and was found to be unrelated to warhead structure. In a related study, a recently reported thiol bearing fluorophore was investigated as a tool for detection of olefin functionalised proteins using thiol-ene chemistry. A protocol for fluorophore bioconjugation to a model protein was successfully developed and validated. This method has potential for wider adoption in labelling a variety of olefin bearing biomolecules. In the fourth chapter, the development of protein profiling tools incorporating self immolative functional groups was investigated. The development of an activity based probe for deubiquitinating enzymes featuring self-immolative linkers and quenched fluorophores was investigated as a set of dual function fluorogenic activity-based probes. The design and synthesis of two novel warhead motifs was accomplished, however, neither motif could be demonstrated as part of an effective probe for protein profiling. In a related study, the first example of a mechanism-based probe for deubiquitinating enzymes is described. A warhead capable of forming an aza-quinone methide electrophile upon probe metabolism was synthesised and successfully incorporated into a ubiquitin construct. In a proof-of-concept labelling experiment in multiple cell lysates, probe metabolism was detected, and several specific protein labelling bands were found. Further work is required to characterise labelled enzymes. This mechanism based probe offers a method for profiling both cysteine protease and JAMM metalloprotease deubiquitinating enzymes and is therefore a powerful addition to the existing suite of activity-based probes. In the fifth chapter, conclusions from each topic are summarised and opportunities for future investigation are outlined. A set of novel chemical probes are suggested based upon the findings reported here, which may prove to be interesting targets for future study. In the sixth chapter, characterisation data and experimental procedures are reported for the chemical modalities and methods described in this thesis. In summary, three topics of investigation are reported: a set of affinity-based probes for profiling the metalloproteome, studies to expand the scope of the thiol-ene reaction, and a set of self-immolative activity-based probes for profiling deubiquitinating enzymes. Emerging from each topic is a novel chemical modality or method which expands the chemical biology toolbox and enables greater understanding of the intricate protein environment of the cell.
APPROVED
Keywords: chemical biology; protein profiling; activity-based probes; affinity-based probes; ubiquitin; deubiquitinating enzymes; enzyme labelling; metalloproteins; metalloenzymes